2014
DOI: 10.5123/s1679-49742014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Vigilância epidemiológica da doença de Chagas no estado de São Paulo no período de 2010 a 2012

Abstract: Objetivo: descrever os indicadores da vigilância epidemiológica da doença de Chagas no estado de São Paulo, Brasil. Métodos: foi realizado estudo descritivo dos indicadores entomológicos e epidemiológicos obtidos a partir das atividades desenvolvidas pela Superintendência de Controle de Endemias (Sucen) no período de 2010 a 2012. Resultados: foram realizadas 3.867 notificações de insetos, dos quais 72,0% eram triatomíneos; das 2.785 notificações de triatomíneos recebidas, as pesquisas realizadas nos atendiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In a study of epidemiological surveillance in Sao Paulo between 2010 and 2012, Silva et al . 20 found that this species was the most important vector of Chagas disease in the State, a finding reflected in its increasing domiciliation and high natural-infection index (23.6%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study of epidemiological surveillance in Sao Paulo between 2010 and 2012, Silva et al . 20 found that this species was the most important vector of Chagas disease in the State, a finding reflected in its increasing domiciliation and high natural-infection index (23.6%).…”
Section: Discussionmentioning
confidence: 94%
“…In Sao Paulo and other States, it is found mainly in cerrado (savannah-like grasslands) biomes. It is the most captured vector of Chagas disease, and there have been numerous reports of the species in chicken coops in peridomestic areas with a low T. cruzi infection rate 16 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In São Paulo, P. megistus presents a restricted distribution range, in which its survival is favored by the rainfall regime, greater humidity and type of vegetation cover, being associated with marsupials of the Didelphidae family and rodents, resulting in a high rate of natural infection (Silva et al, 2014). This species can colonize the human environment and associate with dogs, cats, marsupials, rodents, cattle, goats and swine, among others, as has already been described in the case of T. cruzi infection (Carcavallo et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the interruption of vector-borne transmission was recognized by the Pan-American Health Organization (PAHO) in 2006, and in São Paulo state this condition had already been verified in the 1970s 13 .…”
Section: Comunicação Saúde Educação 2018; 22(64):87-96mentioning
confidence: 99%